2010
DOI: 10.1111/j.1532-950x.2010.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Canine Stifle Kinematic Data Collected with Three Different Targeting Models

Abstract: The JCS model provided sagittal plane flexion/extension data as well as internal/external rotation and abduction/adduction data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 25 publications
1
65
0
Order By: Relevance
“…Other methods such as such as principle component analysis, 32 polynomial equations, 33,34 Fourier analysis, 16,[35][36][37] and generalized indicator function analysis 38 have all been successfully used to study gait waveforms, and use of those methods might have identified differences among the 3 groups of dogs that were undetectable by the discrete variable analysis used. Other methods such as such as principle component analysis, 32 polynomial equations, 33,34 Fourier analysis, 16,[35][36][37] and generalized indicator function analysis 38 have all been successfully used to study gait waveforms, and use of those methods might have identified differences among the 3 groups of dogs that were undetectable by the discrete variable analysis used.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods such as such as principle component analysis, 32 polynomial equations, 33,34 Fourier analysis, 16,[35][36][37] and generalized indicator function analysis 38 have all been successfully used to study gait waveforms, and use of those methods might have identified differences among the 3 groups of dogs that were undetectable by the discrete variable analysis used. Other methods such as such as principle component analysis, 32 polynomial equations, 33,34 Fourier analysis, 16,[35][36][37] and generalized indicator function analysis 38 have all been successfully used to study gait waveforms, and use of those methods might have identified differences among the 3 groups of dogs that were undetectable by the discrete variable analysis used.…”
Section: Discussionmentioning
confidence: 99%
“…Markers were attached with double-sided, adhesive tape (Supa Brands, Worsley, Manchester, UK). A uniplanar, linear kinematic model was used (Thorup et al, 2008;Torres et al, 2010). The method was previously validated for gait parameter repeatability in a study by Stavrakakis et al (2013a) with 1.4 to 3.8°and 1.7 to 4.8°mean differences between repeated marker placements for elbow and knee angle measures, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, a static or anatomic trial of each dog was collected, as described previously 10 . Four markers (noted by an asterisk in Table 1) were removed during subsequent dynamic trials.…”
Section: Methodsmentioning
confidence: 99%
“…Our purpose was to evaluate the effect of marker placement on 3‐dimensional kinematics of the canine stifle with the use of 3 distinct marking systems 10 . Our hypotheses were that marker placement error of a single marker during dynamic gait testing will result in detectable differences in gait data.…”
mentioning
confidence: 99%